The implications of the presence of osteomyelitis on outcomes of infected diabetic foot wounds. (July 2013) - Mutluoglu, Mesut; Sivrioglu, Ali Kemal; Eroglu, Murat; Uzun, Gunalp; Turhan, Vedat; Ay, Hakan; Lipsky, Benjamin A.
Abstract Aim: To assess the effect of the presence of osteomyelitis in patients with a diabetic foot infection. Methods: We reviewed the records of diabetic patients hospitalized at our medical center for a foot infection over a 2-y period. Using clinical, imaging, and microbiology results, we classified each patient as having diabetic foot osteomyelitis (DFO) or not. We then compared several outcome criteria of interest between the 2 groups. Results: Among 73 eligible patients, 37 were in the DFO group (DFO group), while the other 36 were in the soft tissue infection group (STI group). In comparison to the STI group, the DFO group had a significantly longer length of stay (LOS) in the hospital (42 (28.5–51) days vs 19.5 (13.2–29.5) days, p < 0.001), longer duration of antibiotic therapy (46.6 ± 19.9 days vs 22.0 ± 14.6 days, p < 0.001), longer duration of intravenous antibiotic therapy (32.3 ± 16.3 days vs 13.6 ± 14.3 days, p < 0.001), longer duration of wound before admission (44 (31–64.5) days vs 33 (23–45.5) days, p = 0.034), and longer time to wound healing (239.8 ± 108.2 days vs 183.1 ± 73 days, p = 0.011). There were more surgical procedures in the DFO group than in the STI group (24/37 (64.8%) vs 11/36 (30.5%), p = 0.003), and during hospitalization, 22 patients in the DFO group and 5 patients in STI group underwent minor amputation (59.4% vs 13.8%, p < 0.001). Conclusion: The presence of osteomyelitis negatively affects both the treatment and outcome of diabetic foot infections.